Expectations and Experiences of Participants in Ongoing Adoption Reunion Relationships:A Qualitative Study - Affleck, M.; Steed, Lyndall (American Orthpsychiatric Association, Inc, 2001)
This article describes the expectations, responses to unmet expectations, and factors that influence adoption reunion outcomes. Themes derived for interviews with 10 adult adoptees and 10 birth mothers who had each experienced an adoption reunion beyond an initial face-to-face meeting are reported.